The Effect of Ease of Use, Benefits, and Risks on QRIS Usage Intention with Trust as Moderator - Al Ansori, Much Musyarief; Lestari, Endah Prapti (LifeSciFi, 2025)
This study aims to analyze the influence of perceived ease of use, perceived benefits, and perceived risks on the intention to use QRIS (Quick Response Code Indonesian Standard) in Semarang City, while also evaluating the role of trust as a moderating variable. The background of this research lies in the increasing adoption of digital payment systems in urban environments and the need to understand the behavioral drivers that shape user acceptance. Employing a quantitative explanatory approach, this study uses Partial Least Squares–Structural Equation Modeling (PLS-SEM) for data analysis. A total of 200 active QRIS users in Semarang participated in the survey. The findings indicate that both perceived ease of use and perceived benefits significantly and positively influence the intention to use QRIS. Perceived risk also shows a positive but weaker impact. Trust does not moderate the relationship between perceptions and intention to use, nor does it directly affect intention. However, trust is significantly influenced by ease and benefits, but not by perceived risk. These results refine the Technology Acceptance Model (TAM) and suggest that promoting usability and visible benefits is key to accelerating digital payment adoption.